Tersebut EFEKTIVITAS STRATEGI PARAPHRAS DALAM MENINGKATKAN KOMPREHENSI MEMBACA DAN PENCAPAIAN MENULIS - Diah Maulidya Hans (State Institute for Islamic Studies IAIN of Metro, 2014)
Reading comprehension and writing as the crucial skills must be instructed effectively in order to engage the students in the meaningful teaching and learning process. One of the ways to increase students’ reading comprehension and writing achievement is by the use of paraphrasing strategy in the classroom instruction. Through the application of the paraphrasing strategy, it is easy for the students to internalize the information of the original source comprehensively; thus, students’ reading comprehension achievement is increased. In relation to the improvement of students’ reading comprehension achievement, students’ writing achievement is also increased by the use of paraphrasing strategy since the students can rewrite the text in to their own writing style. Therefore, the use of paraphrasing strategy is considered as one of the beneficial ways used to enhance students’ reading comprehension and writing achievement.